Organize And Manage the Processes of Formation of Students ' Skills in Social Activities - Mirzakho'jayeva Dilrabokhon To’lqin qizi (Genius Journals, 2022)
A number of scientific researches are carried out in the world on improving the technology of development of social activity of students of higher educational institutions, development of new pedagogical tools for supporting their social initiative, development of skills of effective organization of socio-cultural and communicative activities. As the main factors for the development of social activity, special recognition of moral-aesthetic outlook and decision-making of political socialization is paid to the students. Also, as pedagogical elements of social activity, the development of technological thinking, conscious attitude to the ideas of development, spiritual and cultural foundations of moral, professional and communicative training of students play an important role. In this article, the role of motivation and motivation in the formation of skills of social activity in students and the importance of their application to practice were investigated on a scientific basis
Keywords: Motivation; processes; activity; method